Optimization of the elicitation process on chrysanthemum indicum cell suspension culture producing xanthine oxidase inhibitor - Amid, Azura; Jamal, Parveen (Asian Network for Scientific Information, 2009)
This research reports the study that aims to enhance the activity of xanthine oxidase inhibitor, a secondary metabolite, found in Chrysanthemum indicum and to identify the most suitable elicitors with the optimize elicitation time and concentration. Many plant species are well known source of secondary metabolite with a variety of biological activities. Production of biologically active compounds using plant cell suspension culture approach, normally gives low result. Optimization studies to enhance xanthine oxidase inhibitor activity using different elicitor concentrations for three different types of elicitor (chitosan, yeast extract and Aspergilus niger) were investigated. A factorial design was used from MINITAB software for optimization of the process. Analysis of results proved that chitosan is the best elicitor to increase activity of xanthine oxidase inhibitor in C. indicum to 1.457 fold higher than the unelicited. The highest xanthine oxidase activity was obtained by chitosan elicitation at concentration of 0.16 g L-1 and it was elicited at 1.25 day cultivation or at 30 h culture with percentage inhibition of 61.818%.